Pharmacognostical and Phytochemical Studies and Biological Activity of Curculigo latifolia Plant Organs for Natural Skin-Whitening Compound Candidate - Syamsu Nur; Heri Setiawan; Muhammad Hanafi; Berna Elya (The Scientific World Journal)
Curculigo latifolia (family Amaryllidaceae) is used empirically for medicinal purposes. It is distributed throughout Asian countries, especially Indonesia. This study aimed at standardizing the C. latifolia plant, analyzing its phytochemical profile, and evaluating its pharmacological effects. The powder from each organ (root, stem, and leaves) was standardized organoleptically and microscopically. Samples were extracted by graded maceration using hexane, ethyl acetate, and ethanol. The extracts were determined for total phenolic content (TPC) and total flavonoid content (TFC). Antioxidant (radical scavenging and metal ion reduction) and antityrosinase activities were determined by spectrophotometric methods. Extracts were analysed for phytochemical profiles by LC-ESI-MS. The highest TPC and TFC were found in the ethanolic extract of the root organ (68.63 ± 2.97 mg GAE/g) and the ethyl acetate extract of the stem (14.33 ± 0.71 mg QE/g extract). High antioxidant activities were found in the ethanolic root extract (20.42 ± 0.33 µg/mL) and ethanolic stem extract (45.65 ± 0.77 µg/mL) by DPPH• and NO• assays, respectively. The ion reduction activity (by CUPRAC assay) was most significant in the ethyl acetate stem extract (390.42 ± 14.49 µmol GAEAC/g extract). Ethanolic root extract was the most active in inhibiting tyrosinase (IC50 value of 108.5 µg/mL). The correlation matrix between TPC and antioxidant activities showed a moderate to robust correlation, whereas the TPC and antityrosinase activity showed a robust correlation. The TFC and antioxidant or antityrosinase activities showed a weak to moderate correlation. The LC-ESI-MS data identified major phenols in the active extracts, including methyl 3-hydroxy-4-methoxy-benzoate, quercetin, 4-O-caffeoylquinic acid-1, and curculigoside. Overall, this study suggests that extracts from the C. latifolia plant offer potent antioxidant and antityrosinase activities, allowing them to be used as natural antioxidants and candidates for skin-lightening compounds.